Search for neutral resonances decaying into a Z boson and a pair of b jets or tau leptons - (:unkn) unknown (ELSEVIER, 2016)
A search is performed for a new resonance decaying into a lighter resonance and a Z boson. Two channels are studied, targeting the decay of the lighter resonance into either a pair of oppositely charged tau leptons or a b (b) over bar pair. The Z boson is identified via its decays to electrons or muons. The search exploits data collected by the CMS experiment at a centre-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 19.8 fb(-1). No significant deviations are observed from the standard model expectation and limits are set on production cross sections and parameters of two-Higgs-doublet models. (C) 2016 The Author. Published by Elsevier B.V.
Keywords: CMS; Physics; Higgs; 2HDM; BSM; b-Tagging; Tau; Lepton; MODEL